On the Endogenous Allocation of Decision Powers in Federal Structures - Jens Oliver Lorz; Gerald Willmann (Kiel Institute for World Economics (IfW), 2004)
This paper provides a political-economy explanation of the degree of centralization in economic policy making. To determine which policies are to be centralized, regions select representatives who then negotiate the degree of centralization and the regional cost shares of centrally decided policies. We show that the resulting degree of cen- tralization is suboptimally low. Voters strategically delegate to repre- sentatives who are averse to public spending and hence prefer decen- tralized decisions in order to reduce their region's cost share. When spill-overs are asymmetric, strategic delegation is stronger at the pe- riphery than at the center.
Keywords: H77; H11; H41; 330; Political Economy; Fiscal Federalism; Endogenous Centralization; Constitutional Design; Zentralstaat; Föderalismus; Finanzföderalismus; Lokales öffentliches Gut; Public Choice; Spillover-Effekt; Verfassung; Theorie